Effects of ROS progenitors on the sporophytic development of maize microspores - Ambrus, Helga (Acta Biologica Szegediensis, 2005)
The sporophytic development of maize microspores was investigated in anther culture under oxidative stress conditions. The oxidative stress was induced using ROS progenitors such as paraquat (Pq) and menadione (Men), methionine combined with riboflavin (Men+Rib) and tert-butylhydroperoxide (t-BHP). All the ROS progenitors reduced the anther response and the number of surviving microspores, which was manifested in a decrease of the number of microspore-derived structures (MDS) in 7- and 30-day-old cultured maize anthers. The ROS progenitors also reduced the regeneration potential of MDS. Numerous abnormal cell divisions and progeny cell degradation could be observed during the development of microspores treated with paraquat, menadione and methionine+riboflavin. Intense nuclear condensation was also found in 7-day-old microspores treated with menadione and paraquat. Moreover, menadione significantly delayed the formation of microspore-derived structures and increased the proportion of embryos. Although a less drastic effect on microspore development was observed in the t-BHP treatment, it increased the ratio of calli in the microspore-derived structures.